Modified Moghissi Cervical Mucus (Cm) Score and Body Mass Index (BMI) in Spontaneous and Clomiphene Citrate Ovulation Induction Program - Al-Janabi, Adnan S.; Hussain, Sabah Mahdi; Rashed, Israa Abdulla (Sulaimani Journal for Pure and Applied Sciences, 2008)
A comparative study was performed to determine the effect of clomiphene citrate (CC) on cervical mucus (CM) sampled in the preovulatory period in ovulatory cycle patients (control) and CC treated patients, moreover the correlation between CM score and body mass index (BMI) was studied in these two groups. One hundred-three infertile women were evaluated in outpatient clinic attending Institute for Embryo Research and Infertility/University of Al-Nahrain/Baghdad from February to August 2005, these patients were divided into two groups, the first group (number= 45) was ovulatory (control) group, this group took no treatment and the second group(number= 58)was CC-treated group, they were given dose of CC 100 mg/day orally for 5 days starting from cycle day 2 .Follicular growth was monitored in both groups starting from cycle day 10 using transvaginal ultrasound when the dominant follicle size was 1620 mm, the CC score was done to all patient. Body mass index (kg/m2) was measured for the all patients and its effect on CM score was evaluated. There was highly significant reduction in volume, consistency, spinnbarkeit, cellularity, and total CM score in treated CC cycles compared to control cycle, whereas there was no statistically significant difference in regard to ferning test between two groups. The PH of CM of patients in the CC treated cycle increased but not to a significant level as compared to control cycle. This study also demonstrate a negative linear correlation with CM and BMI in controls cycle, whereas there is no correlation in CC treated cycle .It was concluded from these results that, CC cause a marked reduction in the quality and quantity of cervical mucus.
Keywords: Cervical mucus score; clomiphene citrate; body mass index